Multivariate Analysis of Confined Groundwater Hydrochemistry of a Long-Exploited Sedimentary Basin in Northwest China - Xuedi Zhang; Hui Qian; Hao Wu; Jie Chen; Liang Qiao (Journal of Chemistry)
A series of environmental and geological problems have been caused by overexploitation of confined aquifers (i.e., deep groundwater) in the Yinchuan region, northwest China. Accordingly, the characteristics of confined water were analyzed and collected from 33 sampling wells in spring of 2011, to determine the factors that influenced the composition and evolution of confined water, using principal component analysis (PCA), correlation analysis, groundwater evolution, and mineral dissolution/precipitation analysis. PCA showed that the hydrochemistry of confined water is controlled mainly by the dissolution of minerals, mixing between the confined aquifer and polluted phreatic water, and effects of ion exchange in the study area. The following management actions recommended were essential, in order to enable the sustainable exploitation of confined water: (1) gradually decreasing the amount of groundwater pumped from confined aquifer in the central part of the depression cone, (2) upgrading the quality of phreatic water, and (3) increasing artificial recharge of the groundwater system by flood waters in the Helan leaning pluvial plain.